Relationship between CO2 Emissions and Renewable Energy Production in the United States of America - Yaw A. Twumasi (Archives of Current Research International, 2017)
This study investigates the relationship between carbon dioxide (CO2) emissions and renewable energy production. In particular, the analysis considers whether there is a uniform relationship between CO2emissions and renewable energy production in the United States. The study uses CO2 emissions, Gross Domestic Product (GDP), population, and renewable energy production data obtained from the U.S. census Bureau, U.S. energy information administration (EIA), and other reliable data sources. Multivariate analysis was combined with geographic information system (GIS) to visualize the variables in each state. Pearson Correlation Coefficient was also used in this study to probe into the relationship between CO2 emissions, renewable energy production, GDP and population in a linear form. Results of this study through the data analysis revealed there was a significant positive correlation between population and CO2 emissions, while GDP also showed positive correlation with CO2 emissions. However, there was no specific pattern between renewable energy and CO2 emissions; meaning that producing more renewable energy does not necessarily lead to less CO2 emissions.